NEW RELATIONSHIPS BETWEEN HERO AND ERA, CHARACTER AND CIRCUMSTANCES - A. I. Ziyadullayev (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the poetic originality of Alfred de Musset’s "The Expression of the Child of the Century", the disproportion of the characters with the society and the contradictions of the plot are analyzed using hermeneutic methods and studied based on different approaches. The "plague of the century" in the work and its impact on society and youth education have been studied, analyzed and some comments have been made. The main idea of the work is the analysis of the images of the characters and episodes of the society in decline after adapting to the times and conditions.